2020
DOI: 10.3389/fvets.2020.00329
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobials Used in Backyard and Commercial Poultry and Swine Farms in the Philippines: A Qualitative Pilot Study

Abstract: Chicken and pork are the most frequently consumed meat products in the Philippines. Swine and poultry are reared in either commercial farms (CMf) or backyard farms (BYf); the latter production system is relatively common and essential to food security in low- and middle-income countries (LMICs) such as the Philippines. Similar to resource-limited LMICs, antimicrobial use (AMU) surveillance has not yet been established; thus, AMU in food animals is a knowledge gap in understanding the emergence of antimicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Antibiotic resistance to colistin would render this life-saving medication ineffective for those with sepsis and pneumonia in intensive care units, including those with severe COVID-19 disease super infected with multidrug resistant bacteria [ 15 ]. The levels of tylosin and colistin use in Nepal are almost double to triple that seen in other Asian countries like the Philippines and Vietnam [ 16 , 17 ]. In a survey of 39 poultry farms in the Philippines, colistin use was 13%, while for tylosin this was only 8% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic resistance to colistin would render this life-saving medication ineffective for those with sepsis and pneumonia in intensive care units, including those with severe COVID-19 disease super infected with multidrug resistant bacteria [ 15 ]. The levels of tylosin and colistin use in Nepal are almost double to triple that seen in other Asian countries like the Philippines and Vietnam [ 16 , 17 ]. In a survey of 39 poultry farms in the Philippines, colistin use was 13%, while for tylosin this was only 8% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of tylosin and colistin use in Nepal are almost double to triple that seen in other Asian countries like the Philippines and Vietnam [ 16 , 17 ]. In a survey of 39 poultry farms in the Philippines, colistin use was 13%, while for tylosin this was only 8% [ 16 ]. Similarly, in a survey of 102 poultry farms in Vietnam [ 17 ], colistin use was 25.8%, while tylosin was 13.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the knowledge and practices of antibiotic use and resistance among farmers have been conducted in some LMICs (7,26). These studies mostly showed that antibiotic use by farmers was high despite a poor level of knowledge (27)(28)(29)(30), and have been important for guiding interventions to promote prudent use of antibiotics to slow the emergence of resistance (31,32). Such studies have never been conducted in Timor-Leste and would help characterise antibiotic knowledge and use at the farm level so appropriate strategies can be developed to avoid overuse and misuse, and facilitate implementation of the National Action Plan for Antimicrobial Resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance (AMR) in bacterial species and strains is a critical global threat, and has been monitored in animals, humans and the environment through international collaborations aimed at AMR reduction (Gerbin, 2014;Lechner et al, 2020;Singh et al, 2021). The main factors contributing to the emergence of AMR are overuse and misuse of antimicrobials, and the lack of quality control of antimicrobials and active pharmaceutical ingredients in the market (Simba et al, 2016;Tangcharoensathien et al, 2018;Barroga et al, 2020). Also, the multi-faceted nature of the problem includes misconceptions about antibiotic types and AMR; lack of diagnostic facilities; limited availability of alternatives to antibiotics as a means to establish antibiotic-free farms; and insufficient training of veterinarians on AMR and antibiotic prescribing (Lekagul et al, 2021).…”
Section: Introductionmentioning
confidence: 99%